2002
DOI: 10.1128/jvi.76.10.4848-4854.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Inhibits and Misdirects Assembly of Hepatitis B Virus Capsids

Abstract: Hepatitis B virus (HBV) capsids play an important role in viral nucleic acid metabolism and other elements of the virus life cycle. Misdirection of capsid assembly (leading to formation of aberrant particles) may be a powerful approach to interfere with virus production. HBV capsids can be assembled in vitro from the dimeric capsid protein. We show that a small molecule, bis-ANS, binds to capsid protein, inhibiting assembly of normal capsids and promoting assembly of noncapsid polymers. Using equilibrium dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 33 publications
3
125
0
1
Order By: Relevance
“…Capsid Preparation-The dimeric HBV capsid protein assembly domain, Cp149 2 , was expressed in Escherichia coli and purified as described (18). Capsids for dissociation experiments were assembled by adding NaCl to Cp149 2 to final concentrations of 25 M Cp149 2 , 25 mM HEPES, pH 7.5, 2 mM dithiothreitol, 0.5 M NaCl (assembly buffer) then incubating at 4°C for 24 h. Capsids were isolated by SEC using a Superose-6 column equilibrated with assembly buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Capsid Preparation-The dimeric HBV capsid protein assembly domain, Cp149 2 , was expressed in Escherichia coli and purified as described (18). Capsids for dissociation experiments were assembled by adding NaCl to Cp149 2 to final concentrations of 25 M Cp149 2 , 25 mM HEPES, pH 7.5, 2 mM dithiothreitol, 0.5 M NaCl (assembly buffer) then incubating at 4°C for 24 h. Capsids were isolated by SEC using a Superose-6 column equilibrated with assembly buffer.…”
Section: Methodsmentioning
confidence: 99%
“…It has since been extended to more involved scenarios [6,26,27], including a study of the energy landscape underlying assembly [7], that is similar to approaches in protein folding [2] or the energy landscape description of association reactions [21,22,23]. These results have been used to investigate the possibility of inhibiting assembly via an anti-viral drug in the case of Herpes Virus [28]. Related approaches include molecular dynamics studies of viral capsid assembly [13,14], and a molecular dynamics-like formalism that is implemented in connection with a "local rules" mechanism that regulates capsid assembly [1,18].…”
Section: Introductionmentioning
confidence: 99%
“…Bis-ANS, a fluorescent probe that binds hydrophobic residues on protein, has been shown to inhibit in vitro HBV capsid assembly [27]. We showed that this compound also inhibits C1-82 assembly in vitro in a dose-dependent manner (Fig.…”
Section: Inhibition Of In Vitro Assembly Of Hcv Nlpsmentioning
confidence: 64%
“…Bis-ANS was shown to trigger detrimental secondary effects in cells and is therefore not suitable for therapy in its present form [27]. However, the inhibitory effects of this compound confirm that targeting hydrophobic clusters of the core is relevant to the development of assembly inhibitors for HCV NLPs.…”
Section: Inhibition Of In Vitro Assembly Of Hcv Nlpsmentioning
confidence: 99%
See 1 more Smart Citation